2011
DOI: 10.1002/eqe.1157
|View full text |Cite
|
Sign up to set email alerts
|

Seismic collapse capacity of basic inelastic structures vulnerable to the P‐delta effect

Abstract: SUMMARYThe collapse capacity of earthquake-excited inelastic nondeteriorating SDOF systems, which are vulnerable to the destabilizing effect of gravity loads (P-delta effect), is evaluated. In this paper, the collapse capacity of the system subjected to a ground motion is defined as spectral acceleration at its initial structural period, at which the structure becomes unstable. Characteristic structural parameters, which affect the collapse capacity, are identified. Ground motion records of the ATC 63 far-fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 19 publications
3
61
0
Order By: Relevance
“…For the same structural configurations, in Figure 7 the corresponding measure for the recordto-record dispersion σ = ln CC p84 /CC p16 [20], where CC p84 and CC p16 denotes the 84th and 16th percentile, respectively, of the collapse capacity, is depicted. σ is a meaningful measure of dispersion because the record-to-record variability of the collapse capacity can be in general approximated by a log-normal distribution [23], confirmed in [4,3] for PDelta sensitive structures. The outcomes show that σ is proportional to the building flexibility τ and the number of stories n, and it increases as τ and n increases.…”
Section: Non-deteriorating Frame Structures ("Base Case")mentioning
confidence: 96%
“…For the same structural configurations, in Figure 7 the corresponding measure for the recordto-record dispersion σ = ln CC p84 /CC p16 [20], where CC p84 and CC p16 denotes the 84th and 16th percentile, respectively, of the collapse capacity, is depicted. σ is a meaningful measure of dispersion because the record-to-record variability of the collapse capacity can be in general approximated by a log-normal distribution [23], confirmed in [4,3] for PDelta sensitive structures. The outcomes show that σ is proportional to the building flexibility τ and the number of stories n, and it increases as τ and n increases.…”
Section: Non-deteriorating Frame Structures ("Base Case")mentioning
confidence: 96%
“…Adam et al [13][14][15] propose to utilize collapse capacity spectra for the assessment of the collapse capacity of SDOF systems, which are vulnerable to the P-delta effect. In [15] it is shown that the effect of gravity loads on SDOF systems with bilinear hysteretic behavior is mainly characterized by means of the following structural parameters:…”
Section: Collapse Capacity Spectramentioning
confidence: 99%
“…In [15] it is shown that the effect of gravity loads on SDOF systems with bilinear hysteretic behavior is mainly characterized by means of the following structural parameters:…”
Section: Collapse Capacity Spectramentioning
confidence: 99%
See 2 more Smart Citations